Association Between Clinical Backgrounds and Malignant Progression of Suspected Intraductal Papillary Mucinous Neoplasm. Issue 6 (13th July 2022) - Fukushima, Genki; Abe, Kodai; Kitago, Minoru; Iwasaki, Eisuke; Hirata, Aya; Takemura, Ryo; Ishii, Ryota; Yagi, Hiroshi; Abe, Yuta; Hasegawa, Yasushi; Fukuhara, Seiichiro; Hori, Shutaro; et al.
Abstract : Objectives: Some intraductal papillary mucinous neoplasms (IPMNs) have malignant potential and can become pancreatic cancer. The mechanism behind the malignant progression of IPMN remains unknown. We aimed to identify the risk factors and interactions between backgrounds for IPMN. Methods: We retrospectively enrolled 980 patients of pancreatic cancer or suspected IPMN (sIPMN) who underwent endoscopic ultrasound or retrograde cholangiopancreatography. We classified them into pancreatic cancer, high-risk sIPMN, and low-risk sIPMN, and investigated the risk factors for high-risk sIPMN. Results: Smoking habits (odds ratio [OR], 3.74; 95% confidence interval [CI], 2.04–6.85; P < 0.001), serum carbohydrate antigen 19–9 ≥37 U/mL (OR, 6.30; 95% CI, 2.88–13.80; P < 0.001), and family history of cancers (OR, 2.38; 95% CI, 1.30–4.37; P = 0.005) were independent risk factors for high-risk suspected IPMN. Odds ratios of diabetes and neutrophil-to-lymphocyte ratio of 2.45 or greater were significantly higher in patients with a family history of cancer than those without a family history of cancer (OR, 3.28; 95% CI, 0.52–20.80 vs 1.85; 95% CI, 0.78–4.41; OR, 2.44; 95% CI, 0.81–7.34 vs 1.24; 95% CI, 0.67–2.30, respectively). Conclusions: Understanding the interactions between background factors can effectively prevent IPMNs' malignant transformation.